Project Management and Engineering Research AEIPRO 2017 - Ayuso Muñoz, José Luis.; Yagüe Blanco, José Luis.; Capuz-Rizo, Salvador F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This is the Proceedings of the 20th International Congress on Project Management and Engineering, that was held at the Technical University of Cartagena, Spain, from July 13 to 15, 2016. It brings together a collection of recent works of researchers and professionals in the Project Management and Engineering fields of Civil Engineering and Urban Planning, Product and Process Engineering, Environmental Engineering, Energy Efficiency and Renewable Energies and Safety, Labour Risks and Ergonomics. .
Project Management -- Predictive tools for project performance management in the construction industry , by A. Cerezo-Narváez, A. Pastor-Fernández, M. Otero-Mateo, J. Portela-Núñez -- Expanding the knowledge on project management standards: a look to the PMBOK® with dynamic lenses, by V. Hermano, N. Martín-Cruz -- Lean thinking: a useful tool to integrate sustainability into project management, by C. Cruz, O. Otegi , M. Aguilar, L. Fuentes -- Civil Engineering and Urban Planning. Construction and Architecture -- Planning and control of civil engineering works in Peru: current state and improvement proposal, by P. M. Carbajal, E. Pellicer, S. Santos-Fonseca, C. Torres-Machi, P. Ballesteros-Pérez -- Experiences on MEF simulation for linear concrete elements with the ATENA tool, by S. Laserna, E. Alcázar, J. Cervera, J. Montero -- Product and Process Engineering and Industrial Design -- Study on optimization of the tuna-fishing vessel construction project, through productionoriented design, by C. Mascaraque-Ramírez, L . Para-González, D. Moreno-Sánchez -- A novel parallel evolutionary approach for the facility layout problem, by Juan M. Palomo-Romero, Lorenzo Salas-Morera and Laura García-Hernández -- A critical evaluation of cathode materials for lithium-ion electric vehicle batteries, by R. Reinhardt, B. Amante García, L. Canals Casals, S. Gassó Domingo -- Design and structural analysis of a prothesis for an arthroplasty. Definition of the osteointegration grade during the rehabilitation process, by F. Cavas, D. Parras, J. Nieto , F. J. F. Cañavate, D. G. Fernández-Pacheco -- MOTIVA-PRO: Innovation based on users' motivations, by D. Justel, A. Retegi, I. Iriarte, G. Lasa, I. González -- Environmental Engineering and Management of Natural Resources -- Combined system UASB+MBR for the biological elimination of emerging contaminants, organic matter and nutrients in urban waste water, by M. J. Moya-Llamas, M. A. Bernal-Romero del Hombre Bueno, E. D.Vásquez-Rodríguez, A. Trapote, C. M. López-Ortiz, and D. Prats -- Identification of environmental risk areas using pollution idexes and geographic information systems, by J. A. Acosta , M. D. Gómez-López, A. Faz, R. Zornoza, S. Martínez-Martínez -- Energy Efficiency and Renewable Energies -- Review of numerical models for studying the dynamic response of deep foundations for the design and project of wind turbines, by G. M. Álamo, J. D. R. Bordón, F. García, J. J. Aznárez, L. A. Padrón, F. Chirino, O. Maeso -- Development and Characterization of Modulars Ceramic and Metal Elements in Vertical Garden and Ventilades Facades in Buildings, by V. Pérez Andreu , C. Aparicio-Fernández , F. Castilla, J.-L . Vivancos -- Qualitative analysis on risk assessment in photovoltaic installations: case study in the Dominican Republic, by C. Guerrero-Liquet Guido, M. Socorro García-Cascales, Juan M. Sánchez-Lozano -- Optimal thickness for isolating foams in buildings, by P. Arrué , A.C. Cárcel, A.M. Romero, C. Aparicio -- Evaluation of the Biomass Potential in the Region of Murcia (Spain): Application to Heat/Cooling Requirements in Industrial Parks (Enering Life+), by A. Molina-García , J. M. Paredes Parra, M.S. García-Cascales, J. Serrano -- Financing models for sustainable energy communities in the United States of America, by Romero-Rubio , De Andrés Díaz -- Optimization of large offshore wind farms implementation, by Mena Bahamonde -- A computational study of the aerodynamic hiding factor between panels array for the optimization of support structures in solar parks, by R. Escrivá-Pla, C. R. Sánchez-Carratalá -- Safety, Labour Risks and Ergonomics -- Assessment of the thermal stress risk during the construction of a warehouse, by J. L. Fuentes-Bargues, A. M. Revuelta-Arnao, M. C. González-Cruz. .
Keywords: Industrial engineering; Production engineering; Project management; Renewable energy sources; Environmental engineering; Biotechnology; Bioremediation; Energy policy; Energy and state; Sociology, Urban; Industrial and Production Engineering; Project Management; Renewable Energy; Environmental Engineering/Biotechnology.; Energy Policy, Economics and Management; Urban Sociology